ANALYSIS OF PURCHASE INTENTION WITH ATTITUDE TOWARD HALAL PRODUCTS AS A MEDIATING VARIABLE IN THE INDONESIAN ICE CREAM INDUSTRY - Dadan Sumantri; Intan Widura Sakti; Iyan Gustiana (istinbath, 2023)
The COVID-19 pandemic has destroyed most industries, especially the food and beverage sector, where if companies are not careful, they can face mass layoffs and even bankruptcy and company closure due to the pandemic. One affected food and beverage industry is dairy food, namely the ice cream industry. The ice cream industry has been devastated by COVID-19 as industry experts believe that in addition to lockdown restrictions, sales of ice cream are affected by fears or misconceptions that ice cream makes a person vulnerable to COVID-19. To increase consumer buying interest, the Indonesian government created a program to help entrepreneurs get halal certificates more quickly and for free. Numerous research studies have examined consumer attitudes toward halal products because they positively influence their intention to purchase a product to determine whether these halal certifiers can boost purchase intention and attitudes toward them. After all, they positively influence their product buying to determine whether these halal certifiers can encourage purchase intention. The method used in this research is a quantitative approach, using a survey as the data collection method. The respondents of this study are 200. In this study it was successful in stating that the attitude toward halal products can influence purchase intention. In addition, attitude toward the halal product is significantly influenced by halal knowledge and brand trust, not by religiosity factors